Effect of Gaze Angle During the Vertical Video Head Impulse Test Across Two Devices in Healthy Adults and Subjects With Vestibular Loss. Issue 6 (July 2020) - Patterson, Jessie; Rodriguez, Amanda; Barin, Kamran; Janky, Kristen L.
Abstract : Objective: To evaluate the effect of gaze angle on vertical vestibulo-ocular reflex (VOR) gain using two different video head impulse (vHIT) devices in healthy adults and subjects with bilateral vestibular loss (BVL). Study Design: Prospective study. Setting: Hospital research laboratory. Subjects: Twenty-four healthy adults (mean [standard deviation SD] age = 32 [4.8]; 23–42; 8 men) and four subjects with previously diagnosed BVL (mean age [SD] = 32 [8.2]; 21–40; 3 men) participated. Intervention: Vertical canal vHIT was administered with two different devices using three gaze angles (–45 degrees, 0 degree, +45 degrees). These devices have different gain calculation algorithms and different head and gaze angle protocols. Main Outcome Measures: Vertical canal gain and presence or absence of reset saccades. Results: A significant stepwise reduction in vHIT gain was noted as gaze moved away from the plane of the canals stimulated (from –45 degrees to 0 degree, to +45 degrees) for both healthy adults and subjects with BVL. vHIT gain was able to separate the two groups using gaze angles –45 degrees and 0 degree. Conclusions: In spite of their differences in gain algorithm and recommended head position and gaze angle, each device was able to appropriately separate healthy adults from subjects with BVL with high sensitivity/specificity. Abstract : Supplemental Digital Content is available in the text